Mampukah Tata Kelola Perusahaan Yang Baik Mengurangi Penghindaran Pajak ? - Noviari, Naniek; Agung Suaryana, I Gusti Ngurah (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 14 No 2 (2019)DO - 10.24843/JIAB.2019.v14.i02.p11, 2019)
Taxpayers will try to pay the smallest possible tax. One way to reduce taxes is to engage in tax avoidance actions commonly referred to as tax avoidance. One of the causes of this behavior is the presence of an executive character who dares to take risks. The impact of the executive character on tax resignation can be reduced by the implementation of good corporate governance. This research proposes the application of good corporate governance to reduce the impact of an executive character on aggressive tax actions. The population of this study comprises of all manufacturing companies listed on the Indonesia Stock Exchange in 2014–2016. Sampling was done using purposive sampling. 48 observations were picked as the samples. This study involved one independent variable (executive characteristics), one dependent variable (aggressive tax action), and one corporate governance variable. The study used moderated regression analysis. This study found the more aggressive the executive character, the higher the probability of the tax avoidance. Better implementation of good corporate governance results in lower the tax avoidance action. Better implementation of good corporate governance also weakens the influence of the executive character on tax avoidance actions. Keywords : tax avoidance, executive characteristics, good corporate governance